Burns as a Public Health Problem: Consequences and the Need for Professional Training (CIPEEX, 2025)
INTRODUCTION: Burns are injuries caused by external agents on the body surface, which may affect only the skin or, in more severe cases, extend to deeper tissues. They are classified into three degrees according to depth: first-degree burns involve the epidermis, presenting erythema without blisters, mild edema, and pain; second-degree burns affect the epidermis and part of the dermis, with the presence of blisters and intense pain; third-degree burns compromise all skin layers, muscles, and even bones, resulting in necrosis with whitish or dark coloration and absence of pain due to nerve damage. Burns may lead to significant consequences, including work absenteeism, physical, aesthetic, psychological, social, and functional impairments, in addition to nutritional repercussions. They are strongly associated with high morbidity and mortality rates and may also trigger metabolic disorders, increased susceptibility to infections, and long-term impacts on quality of life. OBJECTIVE: To analyze the significance of burns as a public health issue and to emphasize the importance of preparing health professionals for adequate treatment and patient care. METHODS: A literature review was conducted in the SciELO and PubMed databases using the Health Sciences Descriptors (DeCS): “burns,” “wounds,” and “wound healing,” combined with the Boolean operator AND. The inclusion criteria studies published in the last five years, freely available, and written in English or Portuguese. RESULTS: The literature shows that the most frequent causes of burns include exposure to flames, scalds, electrical burns, and chemical burns, with severity determined by both exposure time and lesion depth. Epidemiological data indicate that burns are among the main causes of hospital admissions due to accidents, with higher prevalence in young adults, men, and in domestic environments. Socioeconomic and cultural factors are directly related to the etiology of burns, with greater severity observed in developing countries. Elderly individuals represent a particularly vulnerable group, with higher mortality rates and increased risk of severe complications such as sepsis, hypermetabolism, and multiple organ failure. CONCLUSION: Advances in medical care focused on burn treatment, supportive measures, and wound healing have been fundamental to improving patient outcomes. Nevertheless, while treatment effectiveness is greater in younger populations, elderly patients remain at higher risk of adverse outcomes. This highlights the urgent need for public health policies directed toward prevention and specialized care for this population. Educational initiatives targeting physicians and other health professionals are essential to strengthen clinical practices and improve patient recovery across pre-hospital, hospital, and post-hospital settings.
Keywords: burns; wounds; Wound Healing